The estimation of lentil biological properties, productivity and yield capacity - Kholod, S.; Chetveryk, O.; Liashenko, V.; Khomenko, M. (Scientific Progress & Innovations, 2023)
The value of lentil is presented in the article and the study was conducted as to finding productive samples according to their biological properties, yield indicators and the components in agro-climatic conditions of the Southern Forest-Steppe zone of Ukraine. The research was conducted during 2020–2022 in field and laboratory conditions of V. Ya. Yurieva Ustymivka Experimental Station of Plant Growing of the Institute of Plant Growing, of the National Academy of Agrarian Sciences of Ukraine. 35 lentil samples (Lens culinaris Medik.) from Lebanon were the study material. It has been established that the least variable are the following signs: the duration of seedlings-blooming period and the duration of seedlings-ripening period, while seed weight per plant, the amount of pods on the plant and the amount of seeds on the plant are the most variable signs. The correlation relation between the signs of plant height and the height of the lower pod attachment (r = 0.67), between productivity and the amount of pods on the plant (r = 0.76), and between productivity and the number of seeds per plant (r = 0.84) is the most close positive. In the southern part of the Forest-Steppe of Ukraine, lentil experimental samples formed grain yield from 77 to 167 g/m2. The analysis of the average yield during the study years has shown that the most high-yielding are the following samples: 2009S 96568-1, 09S 83210-08, 2009S 96101-5, 09S 83251-21, ILL 7947, 09S 83253-04. On the average, during the research years, the following lentil samples demonstrated the highest productivity: 2009S 96575-6 (3.0 g/m2), 09S 83210-08 (3.3 g/m2), 09S 83251-21 (2.9 g/m2), 09S 83253-04 (2.8 g/m2). The plant productivity indicators were high owing to both increased amount of seeds and the amount of pods on the plant. Such samples as 09S 83251-21, 09S 83253-04, ILL 7947, 2009S 96578-1, 09S 83210-08, 09S 83259-13 can be singled out as to the combination of a high level of the following signs’ manifestation: the amount of pods on the plant, the amount of seeds in a pod, and thousand-seed weight.